First year reflections: Basic guidelines and future directions - Pep Simo; Mihaela Enache; Jose Maria Sallan; Vicenc Fernandez (Journal of Industrial Engineering and Management (JIEM), 2009)
This issue opens the second volume of the Journal of Industrial Engineering and Management, and with this issue begins our second year of publication. The aim of this editorial is to evaluate the 2008 activities, by presenting the members of the Editorial Board and the reviewers of the journal, as well as by reflecting results of quality, prestige and visibility of the journal, which are derived from the perception of the authors, who have sent us their work. Finally, the main conclusions are drawn and future lines of research for the second volume are presented.
Keywords: 650; JIEM; editorial; future directions; authors' satisfaction